(untitled) (Международный научный журнал «Инженер», 2026)
Reservoirs play an important role in providing water for agriculture and generating energy. After the reservoirs are filled, morphometric changes occur in the reservoir area during operation. As the reservoir fills, the flow rate decreases, resulting in accumulation of suspended sediments and bottom sediments in the stream. Large sediments are concentrated in the upper part, while fine sediments are distributed in the middle and lower parts as the flow velocity decreases, and the size of the mud fractions gradually decreases towards the dam. The article analyses the dynamics of turbidity during the operation of the reservoir using the example of the TMGU O’zan reservoir. The volume of turbidity in 1981-2001 was approximately 1145 million tons, and by 2021 it reached 1744 million tons. Considering the average density of the settling turbidity, today 790 million m3 of the volume is filled with turbidity, which means that 35% of the volume of the O’zan reservoir is filled with turbidity.